2013
DOI: 10.1002/wics.1255
|View full text |Cite
|
Sign up to set email alerts
|

Methods for generating families of univariate continuous distributions in the recent decades

Abstract: There has been a renewed interest in developing more flexible statistical distributions in recent decades. A major milestone in the methods for generating statistical distributions is undoubtedly the system of differential equation approach. There is a recent renewed interest in generating skewed distributions. Generally speaking, the methods developed prior to 1980s may be summarized into three categories: (1) method of differential equation, (2) method of transformation, and (3) quantile method. Techniques d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
88
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 150 publications
(109 citation statements)
references
References 133 publications
(205 reference statements)
0
88
0
Order By: Relevance
“…The T-X{Y} framework provides an easy way for generating distributions of the T-X(W) family introduced by Alzaatreh et al (2013b). Existing methods like the methods of combination reviewed in Lee et al (2013) for generating univariate continuous distributions can be derived using the T-X{Y} framework. T-X{exponential}, T-X{Weibull} and T-X{Rayleigh} can be viewed as families of distributions arising from hazard functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The T-X{Y} framework provides an easy way for generating distributions of the T-X(W) family introduced by Alzaatreh et al (2013b). Existing methods like the methods of combination reviewed in Lee et al (2013) for generating univariate continuous distributions can be derived using the T-X{Y} framework. T-X{exponential}, T-X{Weibull} and T-X{Rayleigh} can be viewed as families of distributions arising from hazard functions.…”
Section: Discussionmentioning
confidence: 99%
“…The interest in developing new methods for generating new or more flexible distributions continues to be active in the recent decades. Lee et al (2013) indicated that the majority of methods developed after 1980s are the methods of 'combination' for the reason that these new methods are based on the idea of combining two existing distributions or by adding extra parameters to an existing distribution to generate a new family of distributions. A brief summary of some methods in the literature that are related to the method proposed in this article is provided.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various extensions of SN(λ) have been proposed and studied (e.g., Arellano-Valle et al 2004;Arnold and Beaver 2002;Arnold et al 2007;Choudhury and Abdul 2011;Balakrishnan 2002;Gupta and Gupta 2004;Sharafi and Behboodian 2008;Yadegari et al 2008). For reviews on skewed normal and its generalization, one may refer to Kotz and Vicari (2005) and Lee et al (2013). Pourahmadi (2007) showed that the skewed normal distribution http://www.jsdajournal.com/content/1/1/16 SN(λ) approaches half-normal as λ → ∞.…”
Section: Introductionmentioning
confidence: 99%
“…in the literature (e.g., Alzaatreh, et al (2013a); Alzaatreh, et al (2013b); Alzaatreh, et al (2012a); Alzaatreh, et al (2012b); Lee, et al (2013)). …”
Section: Introductionmentioning
confidence: 99%